The Push : a novel - Audrain, Ashley, 1982- ([New York] : Pamela Dorman Books/Viking, 2021)
"A tense, page-turning psychological drama about the making and breaking of a family, about a woman whose experience of motherhood is nothing at all what she hoped for--and everything she feared. Blythe Connor is determined that she will be the warm, comforting, supportive mother to her new baby Violet that she herself never had. But in the thick of motherhood's exhausting early days, Blythe becomes convinced that something is wrong with her daughter--Violet rejects her mother, screams uncontrollably, and becomes a disturbing, disruptive presence at her preschool. Or is it all in Blythe's head? Her husband, Fox, says she's imagining things. What he sees is an overwhelmed wife who can't cope with the day-to-day grind. The more Fox dismisses her fears, the more Blythe begins to question her own sanity, and the more we begin to question what Blythe is telling us about her life as well. Then their son Sam is born--and with him, Blythe has the natural, blissful connection she'd always imagined with her child. Even Violet seems to love her little brother. But when life as they know it is changed in an instant, the devastating fall-out forces Blythe to face the truth. Here, we see the making and breaking of a family in crystalline detail, and what it feels like when women are not believed. The Push is a tour de force you will read in a sitting, an utterly immersive pageturner that will challenge everything you think you know about motherhood, about our children, and about what happens behind the doors of even the most perfect-looking families. . "--.
Keywords: Suspense fiction